Cyclic compressive loading activates angiotensin II type 1 receptor in articular chondrocytes and stimulates hypertrophic differentiation through a G‐protein‐dependent pathway. Issue 6 (21st May 2018) - Nakamura, Fumihisa; Tsukamoto, Ichiro; Inoue, Shinji; Hashimoto, Kazuhiko; Akagi, Masao
Abstract : Angiotensin II type 1 receptor (AT1R) appears to have a mechanosensing function in a number of cell types. The purpose of this study was to examine whether AT1R expressed in articular chondrocytes is involved in osteoarthritis (OA) progression in vivo and whether cyclic compressive loading activates the AT1R and stimulates hypertrophic differentiation of chondrocytes in vitro . The relationships between the modified Mankin score for cartilage degeneration and the expression of AT1R and type X collagen (Col X) were studied in mouse knees with OA induced using the destabilization‐of‐medial‐meniscus model. Cyclic compressive loads were applied to cultured bovine articular chondrocytes in three‐dimensional agarose scaffolds. Expression of Col X and runt‐related transcription factor 2 (Runx2) was analyzed using RT‐PCR and western blotting. We dissected the downstream pathway for intracellular signal transductions of AT1R including G‐protein‐dependent and G‐protein‐independent pathways. Positive significant correlations between the Mankin score and the rate of AT1R‐immunopositive cells and between the rates of AT1R and Col X expression were noted. The expression of Col X and Runx2 was increased by compressive loading but suppressed by addition of olmesartan, an Ang II receptor blocker, to the agarose scaffolds. Compressive loading upregulated the phosphorylation of c‐Jun N‐terminal kinase (JNK), Src, and STAT1, but olmesartan significantly suppressed only JNK phosphorylation. We conclude that AT1R expressed by articular chondrocytes may be involved in OA progression in vivo . Mechanical stress can activate AT1R and stimulate hypertrophic differentiation of chondrocytes through the G‐protein‐dependent pathway. AT1R has a mechanosensing function in chondrocytes and may be a new therapeutic target in OA. Abstract : A number of mechanosensing mechanisms affecting chondrocyte metabolism have been proposed, but there is insufficient evidence to show how chondrocytes transmit mechanical stress into intracellular signaling. The results of this study led us to hypothesize that chondrocytes express the angiotensin II type 1 receptor (AT1R) and that a mechanical load activates AT1R to stimulate hypertrophic differentiation through a G‐protein‐dependent pathway.